Transjugular biopsy case report of inferior vena cava hepatocellular carcinoma with intracardiac extension. (2017) - Weinberg, Laurence; Abu-ssaydeh, Diana; Macgregor, Chris; Wang, Jason; Wong, Clarence; Spanger, Manfred; Muralidharan, Vijayragavan
Highlights: Transjugular biopsy of IVC or right sided cardiac masses can be safely performed without sedation or anaesthesia. Transjugular biopsy of right atrial lesions may serve as a minimally invasive technique for definitive tissue diagnosis. Multidisciplinary management is paramount for patients with advanced cirrhosis to prevent morbidity and mortality. Abstract: Background: Diagnosis of hepatocellular carcinoma (HCC) can be established with near certainty by correlating radiological imaging with clinical presentation. However, in the absence of diagnostic certainty, biopsy of liver tissue is mandatory for optimal management. We present our management of a patient with advanced liver disease who presented with an IVC mass extending into the right atrium, with co-existing liver lesions not meeting criteria for an imaging diagnosis of HCC. Case presentation: A 62-year-old male with Child-Pugh C liver cirrhosis presented with decompensated liver failure. Multiple imaging modalities demonstrated an inferior vena cava (IVC) mass extending into the right atrium with co-existing liver lesions not meeting radiological criteria for an imaging diagnosis of HCC. There was no contiguous evidence of HCC in the liver, yet there was extensive tumour burden in the IVC representing a separate metastatic lesion without any indication of direct tumour spread. Under fluoroscopic and angiographic guidance, a biopsy catheter was advanced through the right atrium into the IVC. Histology from the biopsy demonstrated fragments of malignant tumour with features consistent with moderately differentiated HCC without thrombus. Given the poor prognosis associated with metastatic HCC with IVC and intracardiac involvement, a multidisciplinary decision was made with the patient's family for palliation care. Conclusion: Transjugular biopsy of IVC masses can be performed effectively, in an awake patient, without the need for sedation or anaesthesia. Where multiple imaging modalities fail to confirm a diagnosis for liver or IVC pathology, transluminal biopsy can assist with definitive diagnosis and treatment planning.